HALF ADDER UNTUK COUNTER PADA METODE DUMP ACCUMULATOR RFID DENGAN TEKNOLOGI 0.35µm - Ganjar Febriyani Pratiwi; Hamzah Afandi; Dyah Nur ‘Ainingsih (Universitas Muhammadiyah Semarang, 2018)
RFID tags are divided into active RFID tags and passive RFID tags. In this case using a passive RFID tag that is supported by using a 13.56 MHz frequency radio signal. RFID technology is used here to monitor nutrients in the nursery process in the planting medium. The method used in sending data via the 13.56 MHz radio frequency is the Accumulator Dump method. Accumulator dump is a method to change the output of Delta Sigma ADC in the form of serial data into parallel data. The accumulator dump is built from a series of registers and counters. For the counter circuit itself uses a combination of NAND gate circuits, Flip-Flop D circuits and Half Adder (HA) circuits. For the half adder circuit itself, it consists of an EX-OR gate and an AND gate. By using 0.35u technology, this half adder circuit is designed on LT- Spice tools which require an input voltage of 3.3 Volts with 11 PMOS and 11 NMOS, with a value of W = 1u and L = 0.35u to produce the desired output. The frequency of the half adder circuit is 50Hz with a maximum power consumption of 0.00363Watt. Keywords: Tag RFID Pasif, Dump Accumulator, Counter, Half Adder